2020
DOI: 10.1097/md.0000000000021377
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected SARS-CoV-2 cardiorespiratory arrest in a myopathy patient undergoing immunosuppressive treatment

Abstract: Rationale: It is recommended that patients with Rheumatic diseases that are at high risk of developing active infections be screened for Tuberculosis, Hepatitis B, and Hepatitis C before receiving second-line immunosuppressive therapies. With the emergence 2019 novel coronavirus (SARS-CoV-2), expanded guidelines have not been proposed for screening in these patients before starting advanced therapy. Patient concerns: We present an unique circumstance whereas a patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Increasing publications of case series and case reports from centers across the world have now described the efficacy of TPE in over 60 COVID-19 patients that did not respond to initial therapies, with the majority having been treated with corticosteroids. 185 -195 Nearly all describe similar positive physiologic and clinical responses temporally associated with initiation or completion of TPE. Further, 3 retrospective, observational cohort studies including a total of 74 patients treated with plasmapheresis have reported dramatic differences in both extubation and survival.…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 99%
“…Increasing publications of case series and case reports from centers across the world have now described the efficacy of TPE in over 60 COVID-19 patients that did not respond to initial therapies, with the majority having been treated with corticosteroids. 185 -195 Nearly all describe similar positive physiologic and clinical responses temporally associated with initiation or completion of TPE. Further, 3 retrospective, observational cohort studies including a total of 74 patients treated with plasmapheresis have reported dramatic differences in both extubation and survival.…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 99%
“…In this case, coronavirus pneumonitis can mimic, or present as, lupus pneumonitis. Pairing this report with a previously reported case [14], we propose that lupus patients, even when asymptomatic, be tested for COVID-19 prior to initiating immunosuppressive therapy. Specifically, patients with lupus that develop pneumonitis and fail to respond rapidly to conventional treatments should be regarded with a high index of suspicion for coronavirus.…”
Section: Discussionmentioning
confidence: 58%
“…ere is evidence to support the beneficial effects of B-cell targeting and biological agents [12,13]. Anti-inflammatories and steroids are also treatments for coronavirus (COVID-19) [14]. When evaluating a lupus patient with shortness of breath, one must consider non-lupus-related conditions such as infections and viruses, including COVID.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen of the 16 were extubated and discharged while three failed to respond and later died. Increasing publications of case series and case reports from centers across the world have now described the efficacy of TPE in over 60 COVID-19 patients that did not respond to initial therapies, with the majority having been treated with corticosteroids [250][251][252][253][254][255][256][257][258][259][260][261]. Nearly all describe similar positive physiologic and clinical responses temporally associated with initiation or completion of TPE.…”
Section: Salvage Therapymentioning
confidence: 99%